Clinical Values of Serum Platelet-Activating Factor in Hypertensive Disorders Complicating Pregnancy - Shasha Liu; Qianyu Lan; Weiling Li; Jiefang Zhang; Liman Fu; Yanlei Xu; Yuan Li (Kidney & Blood Pressure Research)
Introduction: Serum platelet-activating factor (PAF) was proven to be associated with gestational hypertension. However, the predictive value of serum PAF at early pregnancy for the occurrence and outcomes of hypertensive disorders complicating pregnancy (HDCP) remained unclear. Methods: The demographic and clinical characteristics of patients were compared among the different subgroups. The serum PAF level was determined using an enzyme-linked immunosorbent assay. The predictive value of serum PAF for the occurrence and outcomes of HDCP was evaluated using receiver operating characteristic curve analysis. The correlation of serum PAF with blood pressure was assessed using Spearman analysis. Results: Both systolic blood pressure and diastolic blood pressure were significantly higher in HDCP patients, as well as the serum levels of TNF-α and IL-1β at diagnosis/enrollment, while serum levels of IL-10 showed the opposite trend. Serum PAF levels were significantly higher in patients with HDCP compared to normal pregnant women. Furthermore, serum PAF levels were higher in HDCP patients with mild preeclampsia compared to those with gestational hypertension and even more elevated in HDCP patients with severe preeclampsia at the early pregnancy stage and at diagnosis. In HDCP patients, increased serum PAF levels at early pregnancy and at diagnosis were associated with poor outcomes. Additionally, serum PAF levels could predict the occurrence of HDCP and poor outcomes. Conclusion: Serum PAF from HDCP patients at both the early pregnancy and diagnosis stages could effectively predict the occurrence and outcome of HDCP.